The effect of aggregate condition during mixing on the mechanical properties of oil palm shell (OPS) concrete - Lee, Delsye Teo Ching; Lee, Tansuet (EDP Sciences, 2016)
One of the key characteristics affecting the properties of OPS concrete is the saturation condition of the coarse aggregates used during mixing. In this current study, the effect of different aggregate saturation conditions during mixing on the slump, compressive, flexural and splitting tensile strength of OPS concrete was investigated. Three aggregate saturation conditions were employed, namely saturated-surface-dry (SSD), air-dry (AD) and sun-dry (SD). The results revealed that the SD mix had a higher slump value than AD mix and SSD mix. On the other hand, SSD mix registered better compressive, flexural and splitting tensile strength compared to the AD and SD mix. This suggests that the use of SSD aggregates is more effective in producing higher strength concretes which could be credited to the internal curing provided by the SSD aggregates.